Association between sleep quality with overweight/obesity and other factors among adults in indonesia post-COVID-19 pandemic - Athiya Fadlina; Khoirul Anwar (AcTion: Aceh Nutrition Journal, 2024)
The prevalence of adult overnutrition in Indonesia increased from 26,3% to 35,4% from 2013 to 2018. Poor sleep quality is one of the factors of overnutrition. Poor sleep quality increases appetite and decreases energy expenditure, which leads to weight gain. Sleep quality has also worsened during the COVID-19 pandemic. This study aimed to examine the relationship between sleep quality and the incidence of overweight/obesity in adults post-COVID-19. The design of this study was cross-sectional, and an online survey was used. The questionnaire included the current weight, height, and sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were collected from June to August 2022 in Indonesia, using convenience sampling. A Total of 148 participants completed the questionnaire. The association was analyzed using the Chi-square software. This study found 58,8% of the subjects had poor sleep and 23,6% were overweight/obese. Age, sex, education level, occupation, and marital status were associated with sleep quality. A higher proportion of poor sleep quality was found among overweight/overnutrition participants, but no association was found. In conclusion, no association was found between sleep quality and overweight or obesity. Most subjects had poor sleep quality; thus, further intervention is needed to improve sleep quality.